Three fourths of women of reproductive age in emerging regions of Ethiopia are facing problems in accessing health care - Samrawit Mihret Fetene; Tsegaye Gebremedhin Haile (Scientific Reports, 2023)
Abstract Providing adequate and equal access health care is a key goal towards universal health coverage (UHC), but women continue to confront considerable inequities in accessing healthcare, particularly in the emerging regions of Ethiopia. Therefore, we identified the contributing factors to the problems in accessing health care among women of reproductive age in emerging regions of Ethiopia. Data from the 2016 Ethiopia Demographic and Health Survey were used. A total of 4680 women in reproductive age were included in the final analysis and a multilevel mixed-effect binary logistic regression analysis was done to identify the contributing factors to the problems in accessing health care. In the final model, a p-value of less than 0.05 and adjusted odds ratio (AOR) with 95% confidence interval (CI) were used to declare statistically significant factors. We found that 71.0% (95% CI 69.64–72.24%) of women in reproductive age had problems in accessing health care. Unmarried women (AOR = 1.30 95% CI 1.06–1.59), uneducated (AOR = 2.21 95% CI 1.48–3.30) and attended primary school (AOR = 1.58 95% 1.07–2.32), rural resident (AOR = 2.16 95% CI 1.40–2.02), poor (AOR = 2.95 95% CI 2.25–3.86) and middle wealth status (AOR = 1.74 95% CI 1.27–2.40), women who gave two births (AOR = 1.29 95% CI: 1.02–1.64) and not working (AOR = 1.33 95% CI 1.06, − 1.68) and working in agriculture (AOR = 1.88 95% CI 1.35–2.61) were factors that contributed for the problems in accessing health care. A significant proportion of women of reproductive age in emerging regions of Ethiopia face challenges in accessing healthcare, which places the country far from achieving its UHC targets. This issue is particularly prominent among unmarried, poor and middle wealth status, uneducated, non-working, and rural women of reproductive age. The government should develop strategies to improve women’s education, household wealth status, and occupational opportunities which would help to alleviate the barriers hindering healthcare access for women residing in emerging regions of Ethiopia.